Varieties of capitalism and labour market opportunities for the youth: A comparison of attitudes towards skill formation - Felix Hörisch; Jale Tosun; Julian Erhardt; William A. Maloney (European Journal of Government and Economics (EJGE), 2020)
In this study, we examine the extent to which socio-economic institutions shape young people's perceptions of labour market opportunity structures and their employment attitudes (i.e. skills and retraining). Building on the varieties of capitalism approach, we expect young people (aged 18-35) in coordinated market economies (CMEs) with encompassing welfare states to regard firm- and industry-specific skills as more important than their peers in liberal market economies (LMEs). To assess this proposition, we draw on original survey data and compare young people's employment attitudes in five European countries: the United Kingdom (UK), which represents a typical liberal market economy, and Austria, Denmark, Germany and Switzerland as representatives of coordinated market economies. To what extent do different training regimes in CMEs and LMEs shape individual attitudes towards skill formation? The empirical analysis shows that young people's attitudes with regard to the specificity of skills and the willingness to undertake retraining differ systematically between CME and LME countries and supports our argument that the specific socio-economic institutions matter.
Keywords: J24; P16; P5; P51; M53; 330; country-comparative survey; skill formation; skill specificity; varieties of capitalism; labour market